The Processes of Intelligent Firefighting in Seawater Tunnel: a Case Study of Karnaphuli Tunnel in Bangladesh - Yan Yi; Tao Yang; Songsong Xiao; Xing Liu; Min Deng; Zewen Sun; Zhengyang Fan; Hao Huang (Safety & Fire Technology, 2025)
Aim: In the case under consideration, research was conducted to optimize the design process of fire protection for an underwater sea tunnel to reduce potential fire risks and enhance the resistance of fire protection pipelines to corrosion caused by seawater. Introduction: Designing intelligent fire protection systems is always a key point in the construction process of underwater sea tunnels. Taking the Karnaphuli Tunnel in Bangladesh as an example, the intelligent fire protection design of a typical offshore tunnel was examined. The commonly used fire protection schemes for tunnels were analyzed based on the characteristics of underwater tunnel fires, and a suitable intelligent fire protection system was proposed. In view of the hidden dangers from combustible gases such as CO and H2S that might cause fires in the lowest point of wastewater pumping stations, this study set up a gas detection alarm system and an automatic foam fire extinguishing system at the lowest point. Meanwhile, according to the high chloride ions in the water of the Karnaphuli River in Chittagong, the anti-corrosion problem of fire protection pipes in the underwater highway tunnels was discussed, and the selection of fire-fighting pipes was proposed. Considering the characteristics of marine corrosion, a two-layer anti-corrosion structure with epoxy zinc-based powder coating as the bottom layer and functional coating as the surface layer was adopted. Methodology: Both theoretical and practical research methods were carried out in this article. According to the chemical theory, the anaerobic environment in tunnels with seawater was to produce CO and H2S. Using the experimental analysis on practical monitoring of seawater, it could be concluded that ordinary fire protection pipelines could get corroded easily in seawater. Conclusions: Gas detection alarm and automatic foam fire extinguishing system should be added at the lowest point of the undersea highway tunnel due to the presence of some combustible gases such as CO and H2S. In view of the easy corrosion of fire system pipes in underwater highway tunnels, internal and external plastic-coated steel pipes with hot-melt epoxy powder as the inner coating and 3PE (three-layer structure) as the outer coating should be adopted in the design and construction of intelligent fire protection system in underwater tunnels. Keywords: underwater tunnel, intelligent fire protection, pipeline, anti-corrosion, automatic foam fire extinguishing system